Analisis rasio likuiditas dan profitabilitas kinerja keuangan (studi kasus pada pt sentra food indonesia, tbk) th 2019 - 2023 - Rivanda, Alfina Rosy; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
The goal of this research is to analyze the likuiditas and profitability ratios in order to evaluate the financial performance of PT Sentra Food Indonesia, Tbk for the 2019-2023 period. The following ratios are used for analysis: current ratio, cash ratio, return on assets (ROA), and return on equity. The results show that there is a lack of consistency and profitability, which hinders a company’s ability to meet the demand for jangka pendek while also producing laba from aset and ekuitas. The main cause of this failure is an increase in operational costs and a decrease in economic performance. This study recommends that businesses increase sales, reduce costs, and use innovative business strategies to improve financial stability and profitability. In terms of profitability, both ROA and ROE experienced a sharp decline, from 1.54% and 2.46% in 2019 to -39.90% and -95.12% in 2023, respectively, reflecting significant losses and low efficiency in utilizing assets and equity. The company needs to immediately optimize asset management, control operational costs, and increase cash reserves.